Math Problem Statement

(¬(¬A ∧ ¬B) ∧ (¬A ∨ B)) ∨ (C ∨ (C ∧ B))

Solution

Let's simplify the logical expression:

(¬(¬A¬B)(¬AB))(C(CB))(¬(¬A ∧ ¬B) ∧ (¬A ∨ B)) ∨ (C ∨ (C ∧ B))

Step 1: Simplify the inner part ¬(¬A¬B)¬(¬A ∧ ¬B)

This can be simplified using De Morgan's law:

¬(¬A¬B)=AB¬(¬A ∧ ¬B) = A ∨ B

Now, the expression becomes:

((AB)(¬AB))(C(CB))((A ∨ B) ∧ (¬A ∨ B)) ∨ (C ∨ (C ∧ B))

Step 2: Simplify (C(CB))(C ∨ (C ∧ B))

Using the absorption law C(CB)=CC ∨ (C ∧ B) = C, the second part simplifies to:

(C(CB))=C(C ∨ (C ∧ B)) = C

Now the expression becomes:

((AB)(¬AB))C((A ∨ B) ∧ (¬A ∨ B)) ∨ C

Step 3: Simplify (AB)(¬AB)(A ∨ B) ∧ (¬A ∨ B)

We now apply the distributive property:

(AB)(¬AB)=(A¬A)(AB)(B¬A)(BB)(A ∨ B) ∧ (¬A ∨ B) = (A ∧ ¬A) ∨ (A ∧ B) ∨ (B ∧ ¬A) ∨ (B ∧ B)

Simplifying the terms:

  • A¬A=FalseA ∧ ¬A = \text{False}
  • BB=BB ∧ B = B

Thus, the expression reduces to:

(AB)(B¬A)B(A ∧ B) ∨ (B ∧ ¬A) ∨ B

Now, using the absorption law (AB)B=B(A ∧ B) ∨ B = B and (B¬A)B=B(B ∧ ¬A) ∨ B = B, the expression simplifies to:

BB

Step 4: Combine with the remaining part

The expression becomes:

BCB ∨ C

This is the fully simplified form of the given logical expression.

Final Answer:

BCB ∨ C

Do you want more details or have any questions?

Here are some related questions:

  1. How does De Morgan's law apply in logical expressions?
  2. What is the absorption law in logic?
  3. How does distributive property work in boolean algebra?
  4. Can we simplify CBC ∧ B if we know the truth values of C and B?
  5. How does Boolean logic apply to digital circuits?

Tip: Always look for patterns like contradictions (A¬AA ∧ ¬A) and identities to simplify logic expressions efficiently.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Boolean Algebra
Logic Simplification

Formulas

De Morgan's Law
Absorption Law
Distributive Property

Theorems

De Morgan's Theorem
Absorption Theorem

Suitable Grade Level

Grades 10-12